1994
DOI: 10.1007/bf02303567
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel cancer: A 30-year review

Abstract: A correlation exists between the pathologic stage and the survival rate for adenocarcinoma. The most common recurrence pattern for adenocarcinoma was carcinomatosis, followed in frequency by abdominal wall recurrence. Leiomyosarcoma preferentially metastasizes to the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 7 publications
4
45
1
1
Order By: Relevance
“…Although it remains to be defined, correlation between biallelic mutations and very young cancer might be probable. Studies have shown that both sporadic (20) and HNPCCassociated (13,16) SBCs are more common in males than females, with the latter showing a reported 3:1 ratio of males to females. In the present study, 60% of our enrolled patients were male, yielding a 3:2 ratio of males to females that is relatively consistent with the previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Although it remains to be defined, correlation between biallelic mutations and very young cancer might be probable. Studies have shown that both sporadic (20) and HNPCCassociated (13,16) SBCs are more common in males than females, with the latter showing a reported 3:1 ratio of males to females. In the present study, 60% of our enrolled patients were male, yielding a 3:2 ratio of males to females that is relatively consistent with the previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Survival has not been shown to vary with subsite in small case series from single institutions (Zollinger, 1986;Cunningham et al, 1997;Ojha et al, 2000). Other studies (Ashley and Wells, 1988;Frost et al, 1994) have shown slightly more favourable prognosis for duodenal adenocarcinomas. However, hospital-based series are prone to selection bias.…”
Section: Discussionmentioning
confidence: 84%
“…Primary melanoma of the gastrointestinal tract is a rare tumour; involvement of the alimentary tract is usually secondary to metastatic spread from primary tumours [3]. In an autopsy study Avital et al showed that up to 60% of patients with melanoma have gastrointestinal involvement [4].…”
Section: Discussionmentioning
confidence: 99%